Can survey-based information help to assess investment gaps in the EU? - Pana Alves; Daniel Dejuan; Laurent Maurin (European Investment Bank (EIB), 2019)
This study illustrates how information from micro-level and survey-based databases can be used, along with macroeconomic indicators, to provide a better understanding of corporates' investment obstacles. We investigate impediments to corporate investment across the EU. We use a novel dataset merging firm level data from the European Investment Bank Investment Survey (EIBIS) and hard data from corporations' balance sheet and P&L information. We show that the indicators that can be derived from aggregating qualitative answers on impediments to investment at the country level correlate relatively well with macro-based hard data, commonly used as determinants of investments in macro-based models. Notwithstanding this, the perceptions reported by the corporations tend to be related to firms' specific characteristics: "weaker" firms defined as firms that are smaller, and/or more indebted, and/or less profitable and/or with lower liquidity positions, tend to report more impediments. After controlling for firm specific characteristics, the perceived investment gap remains correlated with the reported impediments. While access to finance is not the most reported obstacle, reporting it has the highest information content. Moreover, the signal intensifies when it is given by "weaker" firms. From a policy point of view, our findings suggest that survey-based information can be a useful input to complement hard data, both macro and micro, and better inform the design of targeted policies to support investment.
Keywords: D22; G30; 330; Investment obstacles; Investment gap; Corporate investment; Investment determinants; Granular data; Probit model; Access to finance; Demand; Regulation; Corporates' balance sheet